Patrick Seale, The struggle for Syria. A study of post-war Arab politics (1945-1958), Oxford University Press, London, 1965. 344 pp. - Silva Castillo, Jorge (Estudios de Asia y África, 1966)
Patrick Seale, The struggle for Syria. A study of post-war Arab politics (1945-1958), Oxford University Press, London, 1965. 344 pp.